Magnesium oxychloride cement-based lightweight wall material and preparation method thereof

By adding liquid foam and rice husk to magnesium oxychloride cement and adopting specific preparation methods, the problems of low carbon sequestration efficiency and insufficient mechanical properties of magnesium oxychloride cement are solved, and efficient CO2 adsorption and excellent thermal insulation performance are achieved.

CN119841616APending Publication Date: 2025-04-18QINGDAO UNIV OF TECH

Patent Information

Application Number
CN202411393794.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Magnesium oxychloride cement has low carbon sequestration efficiency in the air, uneven carbonization, and low mechanical properties after foaming, which limits its wide application.

Method used

By adding liquid foam and rice husk to magnesium chlorine cement and using specific mixing and maintenance methods, a lightweight wall material based on magnesium chlorine cement with low dry density, high compressive strength, low thermal conductivity and high CO2 adsorption rate was prepared.

Benefits of technology

It has achieved the improvement of the mechanical properties and insulation effect of magnesium oxychloride cement-based light wall materials while ensuring low material density and high CO2 adsorption rate, and reduced the carbon footprint of the cement industry.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a magnesium oxychloride cement-based lightweight wall material and a preparation method thereof, and belongs to the technical field of building materials. The magnesium oxychloride cement-based lightweight wall material provided by the invention is prepared from the following raw materials in percentage by mass: 40 to 100 parts of magnesium chloride, 45 to 516 parts of magnesium oxide, 4 to 47 parts of liquid foam, 18 to 62 parts of rice husk and 32 to 160 parts of water. The light weight, heat preservation and sound absorption characteristics of the rice husks are combined with the excellent performance of the foamed magnesium oxychloride cement, so that the performance of the cement can be effectively improved, the resource utilization of agricultural wastes is promoted, and the environment friendliness is good. The result of the embodiment shows that the dry density of the magnesium oxychloride cement-based lightweight wall material provided by the invention is 600-840kg / m < 3 >, the compressive strength is 8-15MPa, the heat conductivity coefficient is 0.1-0.2 W / (m.k), and the CO2 adsorption rate is 29.4-37.6 wt%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of building materials, in particular to a magnesium oxychloride cement-based lightweight wall material and a preparation method thereof. Background Art

[0002] The production process of traditional Portland cement releases a large amount of carbon dioxide, which has a negative impact on the environment. In order to promote the goals of green building and low-carbon development, the research and development and application of new cement-based materials have become one of the research hotspots. Lightly burned magnesium oxide (MgO), as a new cement raw material, has the advantages of low energy consumption and low emissions, and can be used to prepare magnesium oxychloride cement (MOC). Magnesium oxychloride cement has the advantages of high strength, good bonding properties, low thermal conductivity and excellent flame retardancy, and has become an ideal choice for manufacturing lightweight wall and other building materials. However, magnesium oxychloride cement has problems such as low carbon fixation efficiency and uneven carbonization in the air, mainly due to the low CO2 concentration in the atmosphere and the high density of the material, which limits the diffusion of CO2.

[0003] Foamed magnesium oxychloride cement is prepared by adding a foaming agent to magnesium oxychloride cement. Although this can improve the porosity of the material, increase CO2 permeability, carbonization rate and carbon fixation efficiency, the increase in porosity leads to problems such as low mechanical properties in the foamed magnesium oxychloride cement, which limits its widespread application.

[0004] Therefore, how to improve the mechanical properties and reduce the thermal conductivity of foamed magnesium oxychloride cement while ensuring low density and high carbon dioxide adsorption rate has become a technical problem that needs to be solved urgently in this field. Summary of the Invention

[0005] The object of the present invention is to provide a magnesium oxychloride cement-based lightweight wall material and a preparation method thereof. The magnesium oxychloride cement-based lightweight wall material provided by the present invention not only has a low dry density and a high compressive strength, but also has a low thermal conductivity, good thermal insulation effect, and a high carbon dioxide adsorption rate.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The invention provides a magnesium oxychloride cement-based lightweight wall material, which is prepared from the following raw materials, calculated by mass percentage: 40 to 100 parts of magnesium chloride, 45 to 516 parts of magnesium oxide, 4 to 47 parts of liquid foam, 18 to 62 parts of rice husks, and 32 to 160 parts of water.

[0008] Preferably, the density of the liquid foam is 15 to 80 kg / m 3 .

[0009] Preferably, the method for preparing the liquid foam comprises: mixing a foaming agent and water to perform foaming to obtain the liquid foam.

[0010] Preferably, the foaming agent is an animal protein foaming agent or a plant active foaming agent.

[0011] The present invention provides a method for preparing the magnesium oxychloride cement-based lightweight wall material described in the above technical solution, comprising the following steps:

[0012] (1) mixing magnesium chloride, water, magnesium oxide and rice husk to obtain magnesium chloride rice husk slurry;

[0013] (2) mixing the magnesium chloride rice husk slurry obtained in step (1) with the liquid foam and then subjecting the mixture to natural curing to obtain a solid material;

[0014] (3) Carbonization curing is performed on the solid material obtained in step (2) to obtain a magnesium oxychloride cement-based lightweight wall material.

[0015] Preferably, the method of mixing magnesium chloride, water, magnesium oxide and rice husks in step (1) comprises the following steps:

[0016] 1) mixing magnesium chloride and water to obtain a magnesium chloride solution;

[0017] 2) mixing magnesium oxide and rice hulls to obtain a mixture;

[0018] 3) mixing the magnesium chloride solution obtained in step 1) and the mixture obtained in step 2) to obtain magnesium chloride rice husk slurry.

[0019] Preferably, the time for mixing magnesium chloride and water in step 1) is 4 to 8 hours.

[0020] Preferably, the magnesium oxide and rice husks are mixed in step 2) by stirring for 100 to 150 seconds using a planetary cement mixer.

[0021] Preferably, the curing temperature in step (2) is 20±2° C., and the curing time is 6 to 10 hours.

[0022] Preferably, in step (3), the temperature of carbonization curing is 20±2° C., the relative humidity of carbonization curing is 70±5%, the CO2 volume concentration of carbonization curing is 20% to 100%, and the carbonization curing time is 4 to 24 hours.

[0023] The invention provides a magnesium oxychloride cement-based lightweight wall material, which is prepared from the following raw materials, calculated by mass percentage: 40 to 100 parts of magnesium chloride, 45 to 516 parts of magnesium oxide, 4 to 47 parts of liquid foam, 18 to 62 parts of rice husks, and 32 to 160 parts of water. In the present invention, magnesium chloride reacts with magnesium oxide and water to form a hydrated product having a crystalline network structure. This structure has a very strong tower hinge system that can withstand extreme pressure, thereby hardening the magnesium oxychloride cement, improving the strength of the wall material, and having excellent low-temperature resistance and fire resistance. Moreover, compared with silicate cement, magnesium oxide is more energy-efficient and low-consumption. The use of the magnesium oxychloride cement-based lightweight wall material of the present invention can alleviate the serious problem of magnesium damage, which is of great significance to the sustainable development of the environment. By adding liquid foam to the material, a larger pore structure can be formed in the wall material, thereby increasing its specific surface area. On the one hand, it can reduce the weight of the wall material, and on the other hand, it can effectively improve the carbonization efficiency and reduce the carbon footprint of the cement industry. By adding rice husks to the wall material, on the one hand, agricultural waste such as rice husks can be recycled and utilized as a resource. On the other hand, rice husks can improve the thermal insulation and sound absorption properties of the wall material and reduce its density. By controlling the amount of each component, the wall material can have good compressive strength while reducing its density. The results of the examples show that the dry density of the magnesium oxychloride cement-based lightweight wall material provided by the present invention is 600-840 kg / m 3 , compressive strength is 8~15MPa, thermal conductivity is 0.1~0.2W / (m·k), and CO2 adsorption rate is 29.4~37.6wt%. DETAILED DESCRIPTION

[0024] The invention provides a magnesium oxychloride cement-based lightweight wall material, which is prepared from the following raw materials, calculated by mass percentage: 40 to 100 parts of magnesium chloride, 45 to 516 parts of magnesium oxide, 4 to 47 parts of liquid foam, 18 to 62 parts of rice husks, and 32 to 160 parts of water.

[0025] In the present invention, unless otherwise specified, the raw materials used in the present invention are all commercially available products well known to those skilled in the art.

[0026] The magnesium oxychloride cement-based lightweight wall material provided herein comprises 40 to 100 parts by mass of magnesium chloride. In the present invention, the magnesium chloride is preferably magnesium chloride hexahydrate. In the present invention, the magnesium chloride reacts with magnesium oxide and water to form a hydrated product, thereby hardening the magnesium oxychloride cement and exhibiting various excellent properties, including low-temperature resistance and fire resistance.

[0027] As an embodiment, the magnesium chloride may be 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, 95 parts or 100 parts.

[0028] In terms of mass percentage, the magnesium oxychloride cement-based lightweight wall material provided by the present invention includes 45 to 516 parts of magnesium oxide. In the present invention, the magnesium oxide is preferably light-burned magnesium oxide. In the present invention, the toughness of magnesium oxychloride cement can be improved by adding magnesium oxide, and its brittleness can be significantly improved. At the same time, the crystalline phase network structure formed by magnesium oxide, magnesium chloride and water has a very strong tower hinge system and can withstand great pressure, thereby improving the strength of magnesium oxychloride cement; at the same time, compared with silicate cement, light-burned magnesium oxide is more energy-saving and low-consumption. The use of the magnesium oxychloride cement-based lightweight wall material of the present invention can alleviate the serious problem of magnesium damage, which is of great significance to the sustainable development of the environment.

[0029] As an embodiment, the magnesium oxide may be 60 parts, 80 parts, 100 parts, 150 parts, 200 parts, 250 parts, 300 parts, 350 parts, 400 parts, 450 parts or 500 parts.

[0030] The magnesium oxychloride cement-based lightweight wall material provided by the present invention comprises 4 to 47 parts of liquid foam by mass percentage. In the present invention, the density of the liquid foam is preferably 15 to 80 kg / m 3 By adding liquid foam to the material, the present invention can form a larger pore structure in the wall material, thereby increasing its specific surface area. On the one hand, it can reduce the weight of the wall material, and on the other hand, it can effectively improve the carbonization efficiency and reduce the carbon footprint of the cement industry.

[0031] As an embodiment, the liquid foam may be 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts or 45 parts; the density of the liquid foam may be 15 kg / m 3 , 20kg / m 3 , 25kg / m 3 、30kg / m 3 、35kg / m 3 , 40kg / m 3 , 45kg / m 3 , 50kg / m 3 , 55kg / m 3 、60kg / m 3 、65kg / m 3 , 70kg / m 3 , 75kg / m 3 or 80kg / m 3 .

[0032] In the present invention, the method for preparing the liquid foam preferably comprises: mixing a foaming agent and water to foam, thereby obtaining the liquid foam.

[0033] In the present invention, the foaming agent is preferably an animal protein foaming agent or a plant active foaming agent, more preferably an animal protein foaming agent, and further preferably a Jk-30 ​​animal protein foaming agent; the foaming agent is preferably a foaming agent sold by Kaixuan Plastics (Taobao store, shipping place: Huizhou, Guangdong).

[0034] The present invention has no particular limitation on the amount of the foaming agent and water, as long as the density of the liquid foam meets the requirements. As an embodiment, the mass ratio of the foaming agent to water is preferably (5-10): (190-200), more preferably 5:195.

[0035] In the present invention, the foaming is preferably carried out in an air compression foaming machine. The present invention has no particular limitation on the specific model of the air compression foaming machine, and commercially available products well known to those skilled in the art can be used.

[0036] The magnesium oxychloride cement-based lightweight wall material provided by the present invention includes 18 to 62 parts by weight of rice husks. By incorporating rice husks into the wall material, the present invention not only recycles agricultural waste such as rice husks, but also improves the thermal insulation and sound absorption properties of the wall material and reduces its density.

[0037] The present invention has no particular limitation on the particle size of the rice husk, and the particle size can be selected according to the common knowledge of those skilled in the art.

[0038] As an embodiment, the rice husk may be 18 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts or 62 parts.

[0039] The magnesium oxychloride cement-based lightweight wall material provided by the present invention comprises 32 to 160 parts by weight of water. In the present invention, the water is preferably deionized water. In the present invention, water primarily acts as a solvent, providing a reaction environment.

[0040] As an embodiment, the water can be 32 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 70 parts, 80 parts, 90 parts, 100 parts, 110 parts, 120 parts, 130 parts, 140 parts, 150 parts or 160 parts.

[0041] In the present invention, magnesium chloride reacts with magnesium oxide and water to form a hydrated product having a crystalline network structure. This structure has a very strong tower hinge system that can withstand extreme pressure, thereby hardening the magnesium oxychloride cement, improving the strength of the wall material, and having excellent low-temperature resistance and fire resistance. At the same time, compared with silicate cement, magnesium oxide is more energy-efficient and low-consumption. The use of the magnesium oxychloride cement-based lightweight wall material of the present invention can alleviate the serious problem of magnesium damage, which is of great significance to the sustainable development of the environment. By adding liquid foam to the material, a larger pore structure can be formed in the wall material, thereby increasing its specific surface area. On the one hand, it can reduce the weight of the wall material, and on the other hand, it can effectively improve the carbonization efficiency and reduce the carbon footprint of the cement industry. By adding rice husks to the wall material, on the one hand, agricultural waste such as rice husks can be recycled and utilized as a resource, realizing the reuse of waste resources. On the other hand, rice husks can improve the thermal insulation and sound absorption properties of the wall material and reduce its density.

[0042] The wall material provided by the present invention combines the lightweight, heat-insulating and sound-absorbing properties of rice husks with the excellent performance of foamed magnesium oxychloride cement, which can not only effectively improve the performance of cement, but also promote the resource utilization of agricultural waste and has good environmental friendliness.

[0043] The present invention also provides a method for preparing the magnesium oxychloride cement-based lightweight wall material described in the above technical solution, comprising the following steps:

[0044] (1) mixing magnesium chloride, water, magnesium oxide and rice husk to obtain magnesium chloride rice husk slurry;

[0045] (2) mixing the magnesium chloride rice husk slurry obtained in step (1) with the liquid foam and then subjecting the mixture to natural curing to obtain a solid material;

[0046] (3) Carbonization curing is performed on the solid material obtained in step (2) to obtain a magnesium oxychloride cement-based lightweight wall material.

[0047] The invention mixes magnesium chloride, water, magnesium oxide and rice husk to obtain magnesium chloride and rice husk slurry.

[0048] In the present invention, the method of mixing magnesium chloride, water, magnesium oxide and rice husks preferably comprises the following steps:

[0049] 1) mixing magnesium chloride and water to obtain a magnesium chloride solution;

[0050] 2) mixing magnesium oxide and rice hulls to obtain a mixture;

[0051] 3) mixing the magnesium chloride solution obtained in step 1) and the mixture obtained in step 2) to obtain magnesium chloride rice husk slurry.

[0052] The present invention preferably mixes magnesium chloride and water to obtain a magnesium chloride solution.

[0053] In the present invention, the mixing time is preferably 4 to 8 hours, more preferably 6 hours. By controlling the mixing time, the present invention can ensure that the magnesium chloride is completely dissolved in water.

[0054] In the present invention, magnesium oxide and rice hulls are preferably mixed to obtain a mixture.

[0055] In the present invention, the magnesium oxide and rice husk are preferably mixed by stirring in a planetary cement mixer for 100 to 150 seconds, more preferably for 120 to 130 seconds.

[0056] As an embodiment, the planetary cement mixer can be a JJ-5 planetary cement mortar mixer. The present invention has no particular limitation on the specific source of the planetary cement mixer, and commercially available products well known to those skilled in the art can be used.

[0057] As an embodiment, the stirring speed can be 140±2 r / min. The present invention can improve mixing uniformity by controlling the stirring speed.

[0058] After obtaining the magnesium chloride solution and the mixture, the present invention preferably mixes the magnesium chloride solution and the mixture to obtain a magnesium chloride rice husk slurry.

[0059] In the present invention, the magnesium chloride solution and the mixture are preferably mixed by adding the magnesium chloride solution to the mixture and then stirring with a planetary cement mixer for 150 to 240 seconds, more preferably 180 to 210 seconds.

[0060] As an embodiment, the planetary cement mixer can be a JJ-5 planetary cement mortar mixer. The present invention has no particular limitation on the specific source of the planetary cement mixer, and commercially available products well known to those skilled in the art can be used.

[0061] As an embodiment, the stirring speed can be 140±2 r / min. The present invention can improve mixing uniformity by controlling the stirring speed.

[0062] After obtaining the magnesium chloride rice husk slurry, the present invention mixes the magnesium chloride rice husk slurry with liquid foam and then performs natural curing to obtain a solid material.

[0063] In the present invention, the magnesium chloride rice husk slurry and liquid foam are preferably mixed by first stirring at a speed of 70 to 80 r / min for 100 to 150 seconds, and then stirring at a speed of 130 to 140 r / min for 100 to 150 seconds; more preferably, first stirring at a speed of 70 to 80 r / min for 120 seconds, and then stirring at a speed of 130 to 140 r / min for 120 seconds. Through the above stirring method, the present invention can ensure that there is no obvious foam floating and mud lumps in the mixed slurry.

[0064] After mixing, the present invention preferably places the mixed product into a mold for natural curing. The present invention does not specifically limit the specific shape and size of the mold, which can be determined based on the shape and size of the desired wall material. In the present invention, the mold does not need to be covered with plastic wrap.

[0065] In the present invention, the temperature of the natural curing is preferably 20±2°C; the time of the natural curing is preferably 6 to 10 hours. The present invention is beneficial to further improve the mechanical properties of the wall material by controlling the temperature and time of the natural curing.

[0066] As an embodiment, the curing temperature may be 18°C, 19°C, 20°C, 21°C or 22°C; the curing time may be 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h or 10h.

[0067] After curing, the cured product is preferably demoulded to obtain a solid material. The present invention has no particular limitation on the specific operation of demoulding, as long as the solid material and the mold are separated without damaging the solid material.

[0068] After obtaining the solid material, the present invention performs carbonization curing on the solid material to obtain a magnesium oxychloride cement-based lightweight wall material.

[0069] In the present invention, the temperature of the carbonization curing is preferably 20±2° C.; the relative humidity of the carbonization curing is preferably 70±5%; the CO2 volume concentration of the carbonization curing is preferably 20% to 100%; and the carbonization curing time is preferably 4 to 24 hours.

[0070] As an embodiment, the temperature of the carbonization curing may be 18°C, 19°C, 20°C, 21°C or 22°C; the relative humidity of the carbonization curing may be 65%, 68%, 70%, 72% or 75%; the CO2 volume concentration of the carbonization curing may be 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or 100%; the carbonization curing time may be 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h or 24h.

[0071] After carbonization curing, the present invention preferably further includes wet curing the carbonization curing product; the wet curing temperature is preferably 20±2°C; the relative humidity is preferably 70±5%, more preferably 70±2%; and the wet curing time is preferably 20-30 days, more preferably 28 days. Through wet curing, the present invention can further improve the performance of the wall material.

[0072] The preparation method provided by the present invention is simple and can provide a theoretical and practical basis for the development of new low-carbon lightweight wall materials through the preparation process, performance parameters and application fields of foamed rice husk magnesium oxychloride cement. It has low equipment requirements and is conducive to the large-scale promotion of the technical solution.

[0073] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the embodiments described are only some of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0074] Example 1

[0075] A magnesium oxychloride cement-based lightweight wall material is prepared from the following raw materials, calculated by mass percentage: 40 parts of magnesium chloride hexahydrate, 85 parts of light-burned magnesium oxide, 5 parts of liquid foam, 18 parts of rice husks, and 32 parts of deionized water;

[0076] The preparation method of the liquid foam is as follows: 5 parts of a foaming agent and 195 parts of water are mixed in an air compression foaming machine for foaming to obtain liquid foam; the foaming agent is Jk-30 ​​animal protein foaming agent sold by Kaixuan Plastics (Taobao store, shipping place: Huizhou, Guangdong); the density of the liquid foam is 52kg / m 3 ;

[0077] The preparation method of the magnesium oxychloride cement-based lightweight wall material comprises the following steps:

[0078] (1) mixing magnesium chloride, water, magnesium oxide and rice husk to obtain magnesium chloride rice husk slurry;

[0079] (2) The magnesium chloride rice husk slurry obtained in step (1) and the liquid foam are mixed and stirred at a speed of 75 r / min for 120 s, and then at a speed of 140 r / min for 120 s, until no obvious foam floating or mud blocks appear. The mixture is then placed in a mold for natural curing without covering the mold with plastic wrap, and a solid material is obtained after demolding; the natural curing temperature is 20±2° C., and the natural curing time is 8 h;

[0080] (3) subjecting the solid material obtained in step (2) to carbonization curing, and finally to wet curing, to obtain a magnesium oxychloride cement-based lightweight wall material; the temperature of the carbonization curing is 20±2° C., the relative humidity of the carbonization curing is 70±5%, the CO2 volume concentration of the carbonization curing is 20%, and the carbonization curing time is 12 hours; the temperature of the wet curing is 20±2° C., the relative humidity of the wet curing is 70±5%, and the wet curing time is 28 days;

[0081] The method for mixing magnesium chloride, water, magnesium oxide and rice husks comprises the following steps:

[0082] 1) dissolving magnesium chloride in water and letting it stand for 6 hours to obtain a magnesium chloride solution;

[0083] 2) stirring the magnesium oxide and rice husks using a JJ-5 planetary cement mixer at a speed of 140 r / min for 120 s to obtain a mixture;

[0084] 3) adding the magnesium chloride solution obtained in step 1) to the mixture obtained in step 2), and then stirring the mixture at a speed of 140 r / min for 180 s using a JJ-5 planetary cement mixer to obtain a magnesium chloride rice husk slurry.

[0085] Example 2

[0086] A magnesium oxychloride cement-based lightweight wall material is prepared from the following raw materials, calculated by mass percentage: 40 parts of magnesium chloride hexahydrate, 85 parts of light-burned magnesium oxide, 7 parts of liquid foam, 18 parts of rice husks, and 32 parts of deionized water;

[0087] The preparation method of the magnesium oxychloride cement-based lightweight wall material and the preparation method of the liquid foam are the same as those in Example 1.

[0088] Example 3

[0089] A magnesium oxychloride cement-based lightweight wall material is prepared from the following raw materials, calculated by mass percentage: 40 parts of magnesium chloride hexahydrate, 85 parts of light-burned magnesium oxide, 9 parts of liquid foam, 19 parts of rice husks, and 32 parts of deionized water;

[0090] The preparation method of the magnesium oxychloride cement-based lightweight wall material and the preparation method of the liquid foam are the same as those in Example 1.

[0091] Example 4

[0092] A magnesium oxychloride cement-based lightweight wall material is prepared from the following raw materials, calculated by mass percentage: 40 parts of magnesium chloride hexahydrate, 85 parts of light-burned magnesium oxide, 11 parts of liquid foam, 19 parts of rice husks, and 32 parts of deionized water;

[0093] The preparation method of the magnesium oxychloride cement-based lightweight wall material and the preparation method of the liquid foam are the same as those in Example 1.

[0094] Comparative Example 1

[0095] Compared with Example 1, the carbonization curing in step (3) was omitted, and other conditions were the same as those in Example 1.

[0096] Comparative Example 2

[0097] Compared with Example 1, rice husks were omitted, and the carbonization curing in step (3) was omitted in the preparation method. Other conditions were the same as those in Example 1.

[0098] Comparative Example 3

[0099] Compared with Example 1, the liquid foam was omitted, and other conditions were the same as those in Example 1.

[0100] The performance of the magnesium oxychloride cement-based lightweight wall materials provided in Examples 1 to 4 and Comparative Examples 1 to 3 was tested, and the results are shown in Table 1:

[0101] Table 1 Performance of magnesium oxychloride cement-based lightweight wall materials provided by Examples 1 to 4 and Comparative Examples 1 to 3

[0102] <![CDATA[Dry density / kg / m 3 > Compressive strength / MPa Thermal conductivity / W / (m·k) <![CDATA[CO2 adsorption rate / wt%]]> Example 1 839 10.83 0.20 29.35 Example 2 785 9.70 0.18 31.98 Example 3 730 9.05 0.15 35.02 Example 4 683 8.08 0.13 37.54 Comparative Example 1 823 9.60 0.20 0 Comparative Example 2 1000 13.54 0.24 0 Comparative Example 3 1361 22.73 0.27 22.95

[0103] The dry density test method is as follows: the prism samples made of the magnesium oxychloride cement-based lightweight wall materials obtained in Examples 1 to 4 and Comparative Examples 1 to 3 are placed in an electric blast drying oven and continuously dried at 60° C. for 72 hours until the mass of the prism samples is constant. The mass and volume of the dried prism samples are measured to calculate the dry density of the magnesium oxychloride cement-based lightweight wall material. Three prism samples are tested in each group, and the average of the dry density measurement values ​​is calculated as the final test result.

[0104] The compressive strength test method is as follows: The compressive strength test is carried out in accordance with the national standard GB / T 17671-2021 "Test method for strength of cement mortar (ISO method)". A compression testing machine is used during the test, and the loading speed is 2400±200N / s. The prism specimens made of magnesium oxychloride cement-based lightweight wall materials are compressed and folded according to regulations, the failure load is recorded, and the compressive strength of the prism specimens is calculated. Three prism specimens are tested in each group, and the average value of the compressive strength measurement values ​​is taken as the final test result. The preparation method of the prism specimens is the same as the dry density.

[0105] The thermal conductivity test method is as follows: The thermal conductivity test is conducted in accordance with the national standard GB / T 10294-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials - Guarded Hot Plate Method." Samples of the magnesium oxychloride cement-based lightweight wall materials obtained in Examples 1-4 and Comparative Examples 1-3 were placed in an electric blast drying oven and dried continuously at 60°C for 72 hours until the sample mass remained constant. The dried samples were measured using a TC3000 hot wire thermal conductivity meter, and the measurement results were recorded according to the instrument's operating procedures. Two samples were tested in each group, and the average of the thermal conductivity values ​​was taken as the final test result. The sample dimensions were 300 mm × 300 mm × 30 mm.

[0106] The CO2 adsorption rate was tested by subjecting samples made from the magnesium oxychloride cement-based lightweight wall materials obtained in Examples 1-4 and Comparative Examples 1-3 to thermogravimetric analysis (TGA). The CO2 adsorption rate was calculated based on the mass loss of CO2 and water of crystallization in the samples at different temperatures. The sample preparation method was the same as for the dry density.

[0107] From the performance comparison of Examples 1 to 4 in Table 1, it can be seen that with the increase in the amount of liquid foam in the magnesium oxychloride cement-based lightweight wall material, the dry density of the wall material continues to decrease, while the compressive strength and thermal conductivity of the wall material are also continuously decreasing, while the CO2 adsorption rate continues to increase, indicating that the increase in liquid foam can increase the specific surface area of ​​the wall material, thereby forming more void structures inside the wall material. These void structures are filled with gas, which can effectively reduce the transfer of heat and thus improve the thermal insulation performance. At the same time, after the specific surface area of ​​the wall increases, it can come into contact with more carbon dioxide, thereby increasing the adsorption rate of carbon dioxide. At the same time, according to the national standard GB / T 17671-2021 "Test Method for Cement Mortar Strength (ISO Method)", the compressive strength of the wall materials obtained in Examples 1 to 4 of the present invention is in the range of 8 to 15 MPa, which meets the use requirements of lightweight wall materials.

[0108] By comparing Example 1 and Comparative Example 1, it can be seen that when the carbonization curing process is omitted, the compressive strength of the wall material is significantly reduced, indicating that the present invention can not only absorb carbon dioxide through carbonization curing, but also improve the mechanical properties of the wall material.

[0109] By comparing Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that the addition of rice husks can significantly improve the thermal insulation performance of the wall material and also improve the lightweight effect of the wall material, but the compressive strength is reduced.

[0110] By comparing Example 1 and Comparative Example 3, it can be seen that when the liquid foam is omitted, although the compressive strength of the wall material can be greatly improved, its dry density also increases significantly, and its lightweight property is lost. In addition, the thermal conductivity of the wall material increases, and the thermal insulation effect is significantly reduced. At the same time, the CO2 adsorption rate also decreases significantly. This shows that the addition of liquid foam plays an important role in reducing the density of the wall material and improving its thermal insulation performance and CO2 adsorption performance.

[0111] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A magnesium oxychloride cement-based lightweight wall material, which is prepared from the following raw materials, calculated by mass percentage: 40 to 100 parts of magnesium chloride, 45 to 516 parts of magnesium oxide, 4 to 47 parts of liquid foam, 18 to 62 parts of rice husks and 32 to 160 parts of water.

2. The magnesium oxychloride cement-based lightweight wall material according to claim 1, characterized in that: The density of the liquid foam is 15 to 80 kg / m 3 .

3. The magnesium oxychloride cement-based lightweight wall material according to claim 1 or 2, characterized in that: The method for preparing the liquid foam comprises: mixing a foaming agent and water to perform foaming to obtain the liquid foam.

4. The magnesium oxychloride cement-based lightweight wall material according to claim 3, characterized in that: The foaming agent is an animal protein foaming agent or a plant active foaming agent.

5. The method for preparing the magnesium oxychloride cement-based lightweight wall material according to any one of claims 1 to 4, comprising the following steps: (1) mixing magnesium chloride, water, magnesium oxide and rice husk to obtain magnesium chloride rice husk slurry; (2) mixing the magnesium chloride rice husk slurry obtained in step (1) with the liquid foam and performing natural curing to obtain a solid material; (3) Carbonization curing is performed on the solid material obtained in the step (2) to obtain a magnesium oxychloride cement-based lightweight wall material.

6. The preparation method according to claim 5, characterized in that: The method of mixing magnesium chloride, water, magnesium oxide and rice husk in step (1) comprises the following steps: 1) mixing magnesium chloride and water to obtain a magnesium chloride solution; 2) mixing magnesium oxide and rice husk to obtain a mixture; 3) Mixing the magnesium chloride solution obtained in step 1) and the mixture obtained in step 2) to obtain magnesium chloride rice husk slurry.

7. The preparation method according to claim 6, characterized in that: The time for mixing magnesium chloride and water in step 1) is 4 to 8 hours.

8. The preparation method according to claim 6, characterized in that: In the step 2), the magnesium oxide and the rice husk are mixed by using a planetary cement mixer for 100 to 150 seconds.

9. The preparation method according to claim 5, characterized in that: The curing temperature in step (2) is 20±2° C. and the curing time is 6 to 10 hours.

10. The preparation method according to claim 5, characterized in that: In the step (3), the temperature of carbonization curing is 20±2° C., the relative humidity of carbonization curing is 70±5%, the CO2 volume concentration of carbonization curing is 20% to 100%, and the carbonization curing time is 4 to 24 hours.

Citation Information

Patent Citations

  • Magnesium cement foam material

    CN102101787A

  • Lightweight environmental protection glass magnesium board

    CN105174996A

Cited By

  • High-strength flame-retardant foamed magnesium oxychloride composite material and preparation method thereof

    CN121850580A